THE INFLUENCE OF LEARNING DISCIPLINE AND PEER ENVIRONMENT ON LEARNING OUTCOMES OF BUSINESS ECONOMY IN CLASS X AT ONE OF SMK NEGERI IN JAKARTA - Rahmadi, Rico Tri; Zulaihati, Sri; Susanti, Santi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2020)
This research aims to determine the effect of learning discipline and peer environment on learning outcomes of business economics subjects in class X at one of SMK Negeri in Jakarta. The population of this research was 252 students. The sampling technique used proportional random sampling to obtain a sample of 147 students. The results of this research are: (1) There is a positive and significant influence between learning disciplines on learning outcomes as indicated by tcount> ttable which is 5.097> 1.97658. (2) There is a positive and significant influence between the peer environment on learning outcomes as indicated by tcount> ttable which is 3.232> 1.97658. (3) There is a positive and significant influence between learning discipline and peer environment on learning outcomes as indicated by the value of Fcount> Ftable which is 33.833> 3.06.